The VISCACHA survey – IX. The SMC Southern Bridge in 8D - Parisi, Maria Celeste (2024)
The structure of the Small Magellanic Cloud (SMC) outside of its main body is characterized by tidal branches resulting fromits interactions mainly with the Large Magellanic Cloud (LMC). Characterizing the stellar populations in these tidal componentshelps to understand the dynamical history of this galaxy and of the Magellanic system in general. We provide full phase-space vector information for Southern Bridge clusters. We performed a photometric and spectroscopic analysis of twelve SMCclusters, doubling the number of SMC clusters with full phase-space vector information known to date. We reclassify the sampleconsidering 3D distances and 3D velocities. We found that some of the clusters classified as Southern Bridge objects accordingto the projected 2D classification actually belong to the Main Body and Counter-Bridge in the background. The comparison ofthe kinematics of the genuine foreground Bridge clusters with those previously analysed in the same way reveals that SouthernBridge clusters are moving towards the LMC and share the kinematics of the Northern Bridge. Adding to our sample clustersfrom the literature with CaT metallicity determinations we compare the age–metallicity relation of the Southern Bridge withthe one of the Northern Bridge. We reinforce the idea that both regions do not seem to have experienced the same chemicalenrichment history and that there is a clear absence of clusters in the Northern Bridge older than 3 Gyr and more metal poor than−1.1, which would not seem to be due to a selection effect.